Nutritional status and health-related quality of life of breast cancer patients on chemotherapy - Lua, Pei Lin; Zakaria, Noor Salihah; Mamat, Nik Mazlan (Nutrition Society of Malaysia, 2012)
Introduction: Nutritional decline is typically accepted as a consequent of the course of treatment for cancer. This study aimed to (1) assess body weight status and dietary intake of breast cancer patients on chemotherapy and (2) to correlate Body Mass Index (BMI), energy and protein intake with health-related quality of life (HRQoL) profile. Methods: A cross-sectional study was conducted in two government hospitals in the East coast of Peninsular Malaysia using convenience sampling. Women aged >18 years, who were diagnosed with breast cancer and receiving chemotherapy were invited to participate. The following aspects were evaluated: body weight status, usual dietary intake (diet history) and HRQoL (EORTC QLQ-C30). Descriptive statistics and non-parametric tests were employed (SPSS 16). Results: Of the respondents, 41 were 49 ± 9.6 years of age; 92.7% were Malay; 97.6% (response rate = 91%) were on moderately emetogenic chemotherapy. Over half of the patients were overweight or obese (mean BMI = 25.3 ± 1.1 kg/m2). The majority self-reported weight reduction (46.3%) but positive energy balance was detected with the current energy and protein intakes recorded at 1792.6 ± 304.9kcal/day (range= 1200-2500) and 74.5g/day (IqR= 37.7)respectively. Dietary intakes were, however, not correlated with HRQoL, but greater BMI was associated with better emotional and cognitive functioning and less fatigue. Conclusion: Although most patients declared losing weight, obesity and excess dietary intake were noted. Additionally, body weight status has been shown to be important in HRQoL profile, underlining the necessity for effective nutritional assessments and support to the cancer population.